The Determinants Of Social Enterprises Performance In Malaysia And Singapore - Cheah, Sau Seng (2018)
The ultimate mission of a social enterprise is to address the most pressing social or environmental issues in society. However, majority of the social enterprises in Malaysia and Singapore are confronted with the criticality of survival and low performance challenges, especially in financial sustainability. By integrating resource-based view and resource dependence theory, this empirical study established a framework to assess the influence of internal-oriented resources (i.e., entrepreneurial orientation, social salience and business planning), and external-oriented resources (i.e., financial support and training support), which moderated by socio-economic context, towards the financial and social performance of social enterprises.